BUSINESS DISTRIBUTION RESULTS OF SHARIA FINANCIAL INSTITUTIONS IN HADITS PERSPECTIVE - Muzakkir S. (Universitas Islam Negeri Mataram, 2019)
All results of operations managed in a Sharia Financial Institution should use a system that does not harm either party in accordance with applicable accounting standards. The accounting basis is the accounting principle that determines when the effects of transactions or events must be recognized for financial reporting purposes. Which accounting base is used by a particular organization, depending on the policies and conditions that exist. Regardless of which accounting basis is used, this paper will explain both of these accounting bases that exist in practice, both in the private sector and the public sector including government, to review the National Sharia Board Fatwa Number 14 / DSN-DSN / IX / 2000 Concerning Distribution Systems Business Results in Islamic Financial Institutions.The approach used in this paper is the hadith study approach to the legal basis contained in the DSN Fatwa concerning Business Results Distribution System in Islamic Financial Institutions. This approach is expected to be able to describe the conceptual framework related to the legal basis for establishing a fatwa.